PKU mutation p.G46S prevents the stereospecific binding of l‐phenylalanine to the dimer of human phenylalanine hydroxylase regulatory domain. Issue 2 (21st January 2017) - Leandro, João; Saraste, Jaakko; Leandro, Paula; Flatmark, Torgeir
Abstract : Mammalian phenylalanine hydroxylase (PAH) has a potential allosteric regulatory binding site forl ‐phenylalanine (l ‐Phe), in addition to its catalytic site. This arrangement is supported by a crystal structure of a homodimeric truncated form of the regulatory domain of human PAH (hPAH‐RD 1–118/19–118 ) [Patel D et al . (2016) Sci Rep doi:10.1038/srep23748 ]. In this study, a fusion protein of the domain (MBP‐(pepXa )‐hPAH‐RD 1–120 ) was overexpressed and recovered in a metastable and soluble state, which allowed the isolation of a dimeric and a monomeric fusion protein. When cleaved from MBP, hPAH‐RD forms aggregates which are stereospecifically inhibited byl ‐Phe (> 95%) at low physiological concentrations. Aggregation of the cleaved dimer of the mutant form hPAH‐G46S‐RD was not inhibited byl ‐Phe, which is compatible with structurally/conformationally changed βαββαβ ACT domain folds in the mutant. Abstract : Regulatory domain (RD) of phenylalanine hydroxylase (PAH) is expressed as metastable MBP fusion protein both as wt (G46) and a PKU mutation (G46S).l ‐Phe, but notd ‐Phe, stabilizes wt‐RD as a dimer, whereas the mutant RD protein aggregates.